2023
DOI: 10.1111/flan.12716
|View full text |Cite
|
Sign up to set email alerts
|

Cultural representation in German as a foreign language textbooks used in Indonesia: A critical social semiotic analysis

Sjuul Juliana Lendo,
Handoyo P. Widodo,
Sayyidatul Fadlilah
et al.

Abstract: Informed by an integrated critical social semiotic approach, the present critical discourse study investigates the semiotic relations of image–text and the cultural meanings encapsulated in two German language textbooks: Studio d A1 and Netzwerk A1 widely used in Indonesia. Adopting Xiong and Peng's semiotic relation model, the findings demonstrate that Netzwerk A1 provides learners with opportunities to learn, think, and reflect critically on German culture through pedagogical questions regarding image–text‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Many textbook analyses have demonstrated that there is often a risk of producing or reproducing power relations but also stereotypes and prejudices in textbooks and that this needs to be addressed when researching textbooks [27,28]. In our study, the two textbooks deal with students' mental health and well-being, and since they need to follow economicpolitical "orders" (e.g., what is considered acceptable behaviour and thought in mainland China), it is to be expected that students' experiences of Chinese higher education as well as the way their diversity is portrayed could be generalised, stereotyped, and even simplified.…”
Section: Analysing the Power Of Textbooksmentioning
confidence: 99%
“…Many textbook analyses have demonstrated that there is often a risk of producing or reproducing power relations but also stereotypes and prejudices in textbooks and that this needs to be addressed when researching textbooks [27,28]. In our study, the two textbooks deal with students' mental health and well-being, and since they need to follow economicpolitical "orders" (e.g., what is considered acceptable behaviour and thought in mainland China), it is to be expected that students' experiences of Chinese higher education as well as the way their diversity is portrayed could be generalised, stereotyped, and even simplified.…”
Section: Analysing the Power Of Textbooksmentioning
confidence: 99%